2016
DOI: 10.5604/17322693.1222106
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of proton pump inhibitors and its consequences

Abstract: Direct inhibition of H+ ion excretion to the gastric lumen makes proton pump inhibitors (PPI) the most effective drugs against gastric acid-related diseases. Over recent years usage of proton pump inhibitors has increased dramatically. Due to the low costs, high efficacy and rarity of adverse effects, their use is prevalent and often it does not correspond with existing medical guidelines. The literature lists stress ulcer prophylaxis among patients with low risk of bleeding, routine 'gastroprotective' medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The decision to choose an appropriate dosage form rest on several aspects, like the patient's ability to receive oral medicine, the patient's hemodynamic status in addition to intestinal penetrability, and absorptive volume (6). Currently, there has been a trend concerning overutilization of SUP in hospitalized patients because evidence-based implemented guidelines on who should take SUP in patients are not followed consistently (1,7,8). Inappropriate use of medicine was previously documented in this center while evaluating albumin usage's appropriateness (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to choose an appropriate dosage form rest on several aspects, like the patient's ability to receive oral medicine, the patient's hemodynamic status in addition to intestinal penetrability, and absorptive volume (6). Currently, there has been a trend concerning overutilization of SUP in hospitalized patients because evidence-based implemented guidelines on who should take SUP in patients are not followed consistently (1,7,8). Inappropriate use of medicine was previously documented in this center while evaluating albumin usage's appropriateness (9).…”
Section: Methodsmentioning
confidence: 99%
“…Implementing a rational prescribing guideline led to an increase in the inappropriateness of prescriptions and cost reduction. Inappropriate and unsupervised administration of IV pantoprazole can lead to increased therapeutic cost (wastage), adverse effects associated with injection, and also increasing the occurrence of community-acquired pneumonia (10), spontaneous bacterial peritonitis (11), vitamins and minerals malabsorption (12), bone fractures (13), and clostridium difficile infection (6,8,14). Pharmacists encourage appropriate SUP by preparing and applying therapeutic guidelines and educational courses built upon the best accessible evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Segundo Kazberuk et al (2016) na prática, alguns dos usos irracionais mais comuns de medicamentos são prescrições excessivas de antibióticos, inibidores da bomba de prótons (IBP) e glicocorticoides. Desse modo, uma classe medicamentosa que se tornou muito utilizada pela população e merece destaque é a dos Inibidores de Bomba de Prótons (IBPs).…”
Section: Introductionunclassified
“…6 Many drug utilization studies have reported the widespread inappropriate use of PPIs,which could lead to serious and poor health outcomes. [7][8][9][10] Therefore, research is needed to investigate the use of PPIs in clinical settings.…”
mentioning
confidence: 99%
“…The prescription pattern of PPIs has been investigated worldwide, including the Middle East. [7][8][9][10][11][12] Despite the introduction of a standard guideline for prescribing PPIs, findings from the previous studies indicated patients' need for appropriate prescription and use of PPIs. In Saudi Arabia, data related to PPI prescription are limited to those reported in the literature.…”
mentioning
confidence: 99%